2015
DOI: 10.1371/journal.pone.0116217
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Canola (Brassica napus) under Salt Stress at the Germination Stage

Abstract: Canola (Brassica napus) is one of the most important oil crops in the world. However, its yield has been constrained by salt stress. In this study, transcriptome profiles were explored using Digital Gene Expression (DGE) at 0, 3, 12 and 24 hours after H2O (control) and NaCl treatments on B. napus roots at the germination stage. Comparisons of gene-expression between the control and the treatment were conducted after tag-mapping to the sequenced Brassica rapa genome. The differentially expressed genes during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 72 publications
4
35
0
Order By: Relevance
“…From the digital gene expression results, 826 and 224 genes were differentially expressed in CL2 and CL6 in comparison with CK, respectively. Of the DEGs, the down-regulated gene number was higher than the up-regulated gene number in CL2 and in CL6 in comparison with CK, which was opposite of the tendency in Gossypium aridum [65] and in Canola [66]; this phenomenon may be because N. sibirica Pall. is a halophyte.…”
Section: Discussionmentioning
confidence: 77%
“…From the digital gene expression results, 826 and 224 genes were differentially expressed in CL2 and CL6 in comparison with CK, respectively. Of the DEGs, the down-regulated gene number was higher than the up-regulated gene number in CL2 and in CL6 in comparison with CK, which was opposite of the tendency in Gossypium aridum [65] and in Canola [66]; this phenomenon may be because N. sibirica Pall. is a halophyte.…”
Section: Discussionmentioning
confidence: 77%
“…These studies have suggested that differentially expressed genes relating to oxidation-reduction processes and proline metabolism, as well as many transcription factors, all likely play roles in salt tolerance 25, 27 . In a recent study transcriptome-level analysis was used to examine the root responses to salinity in an Indian wheat salt-tolerant variety 29 .…”
Section: Introductionmentioning
confidence: 99%
“…High salinity reduces germination, seedling emergence, and ultimately crop establishment (Stumpf et al 1986;Fowler 1991;Khan and Ungar 1999;Puppala et al 1999;Ashraf 2001;Qasim et al 2003;Ashraf and Foolad 2005;Guma et al 2010;Jamila et al 2010;Zivdar et al 2011). Ahamad et al (2012) reported salinity stress significantly affected the rate of germination, root and shoot growth of four canola cultivars, while Long et al (2015) reported that root growth of canola is affected by salinity stress as early as 12 h post-exposure. Our study confirmed that several parameters need to be considered when examining salinity tolerance, and that no single measure is sufficient when selecting a salinity-tolerant genotype.…”
Section: Salinity (Ec Sol )mentioning
confidence: 99%
“…Qasim et al (2003) observed a sharp increase in proline content in leaves of two canola cultivars, Dunkeld and Cyclone under salinity stress (4, 8, and 12 dS m −1 ) compared with low salinity stress (2 dS m −1 ). Long et al (2015) showed that proline dehydrogenase (ProDH) and Δ1-pyrroline-5-carboxylate synthase (P5CS) were differentially expressed in B. napus under salt stress. Both these enzymes are involved in proline metabolism in plants.…”
Section: Salinity (Ec Sol )mentioning
confidence: 99%